Glycogen content in the eggs of four freshwater teleostean species - Basu, Sajal (Indian Journal of Fisheries, 2011)
Yolk begins to deposite in the egg duringthe period of vitellogenesis (Raven 1961,Kirpichnikov 1981). According to Balinsky(1970), yolk is first synthesized in the liverand then transported in the soluble statethrough the blood stream to the ovary fordeposition in the mature oocytes. The essentialcomponents of yolk are proteins, phospholipids,glycogen and some neutral fats.Importance of glycogen in the normaldevelopment of a vertebrate embryo is wellknown (Spratt 1955,1958a). In the fish egg,this glycogen also acts as the substrate forvarious enzymes for glycolysis and othercarbohydrate metabolism (Milman andJurovtizsky 1973, Shaklee and Whitt 1967).As early development of eggs depends muchon their energy source, the importance ofglycogen in the fish egg needs due weightage.With this view the glycogen contentsof the eggs of 4 teleostean species Mystusvittatus (Bloch), Notopterus notopterus(Pallas), Channa punctatus (Bloch) andChanna striatus (Bloch) were studied andhistochemical tests of glycogen of the 4species were also done.Mature eggs and ovaries